ANALYSIS OF MISCONCEPTION OF STUDENTS ON CLASS SMP MUHAMMADIYAH 12 MAKASSAR ON SET MATERIAL - Kristiawati Kristiawati; Sri Satriani (JURNAL PEMBELAJARAN DAN MATEMATIKA SIGMA (JPMS), 2025)
Misconception is a wrong or inaccurate understanding or comprehension of a concept, information, or phenomenon. The purpuse of this study is to determine the misconceptions experienced by students in the material of sets. This study is a descriptive study with a qualitative approach. The subjects in this study were grade VII students of SMP Muhammadiyah 12 Makassar, selected as many as 3 students, each of whom experiencedthe most dominant theoritical, classification, and correlational misconceptions throught tests given and interviews. The instruments used in this study were tests to see the misconceptions experienced by students and interview guidelines used to confirm the results of student work. The data analysis technique in this study used three stages, namely data condensation, data presentation, and data verification. The results showed that types of misconceptions experienced by students were most dominant theoritical, classification, and correlation misconceptions. The types of misconceptions experienced by subject S1 are included in theoritical misconceptions. Because subject S1 made mistakes in analyzing and defining the form of set operations in the Venn diagram image. The type of misconception experienced by subject S2 is classification misconception. This is in accordance with the indicator of classification misconception, namely the subject is wrong in distinguishing or grouping elements in the set material. The type of misconception experienced by subject S3 is correlational misconception, this is because subject S3 meets the indicator of corellational misconception, namely errors in applying the concept of sets with other mathematical concepts.